2014
DOI: 10.1074/jbc.m114.568832
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl-lactotetra, a Novel Cell Surface Marker of Undifferentiated Human Pluripotent Stem Cells

Abstract: Background: Carbohydrate epitopes are often used as markers for characterization of human pluripotent stem cells (hPSC).Results: Sialyl-lactotetra is highly expressed on the cell surface of hPSC lines, and the expression decreased upon early differentiation.Conclusion: Sialyl-lactotetra is a novel marker of undifferentiated human stem cells.Significance: These findings might impact future applications in regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…In humans SSEA-4 is a marker for embryonic and adult stem cells [ 34 36 ]. Upon differentiation of human embryonic stem cells, the expression of SSEA-4 is rapidly diminished, and has almost completely disappeared after 14 days [ 37 , 38 ], i.e., SSEA-4 downregulation accompanies the loss of pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…In humans SSEA-4 is a marker for embryonic and adult stem cells [ 34 36 ]. Upon differentiation of human embryonic stem cells, the expression of SSEA-4 is rapidly diminished, and has almost completely disappeared after 14 days [ 37 , 38 ], i.e., SSEA-4 downregulation accompanies the loss of pluripotency.…”
Section: Discussionmentioning
confidence: 99%
“…The CID spectrum of m/z 824.5 reveals a mass loss of 80, which is characteristic for a sulfate group, plus the same compounds that can be detected in the case of sterlet at m/z 722.5, i.e., both compounds have similar structures. The fragmentation of m/z 778 resulted in losses of m/z 242 and 256, which are characteristic of a sulfated hexose moiety [42,43]. It is known that sulfated glycolipids can be basically detected in the positive and in the negative ion mode [44].…”
Section: Tandem Ms Experiments To Elucidate the Assignments Of Unknowmentioning
confidence: 99%
“…The target of the TRA-1-60 antibody, the nonsialylated version of the glycan, is an excellent marker for pluripotent stem cells. 30 , 31 , 32 Previous research found sialyl-LacNAc type 1 on glycolipids in malignant glioma 33 and embryonal carcinoma. 34 Pancreatic cancer cells frequently activate developmental pathways, 35 , 36 , 37 potentially leading to the expression of the sialyl-LacNAc type 1 epitope.…”
Section: Discussionmentioning
confidence: 97%